Stasys Ylaʼs Cultural Anthropology: Paradigms of Inhumanity and Resurrection - Mikelaitis, Gediminas (Literatūra, 2018)
[article in Lithuanian; only abstract in English]This article reveals the experiences of dehumanization, i.e., inhumanity and degeneracy, experienced by and described in the works of Prof. Stasys Yla (1908–1983) – cultural historian, psychologist, pedagogue, theologist, writer as well as inmate and priest at Stutthof concentration camp. The article also examines his efforts in remaining as humane as possible and in seeking opportunities for spiritual resurrection. The following works of Yla are studied: the study Communism in Lithuania (Kaunas, 1937, his book of memoirs People and Beasts in the Forest of the Gods (Putnam, US, 1951, re-released in Lithuania in 1991) and a collection of his manuscripts titled Lectures, Sermons and Prayers in Stutthof (written during 1943–1944, re-released in 2018).Having himself experienced the terror of totalitarianism and the brutality induced by propaganda theories, Yla presents a commanding expression of this suffering in his works. Revealing the horror of the total elimination of people that he was a witness to, he not only shows the tragedy of dehumanization but also highlights the anthropological factors that encouraged him to keep his humanity, giving him the chance to experience moments of creativity and nurture his eschatological belief in faith. Yla’s efforts to reveal a person’s psychological transformation and the experiences that express this change are undoubtedly valuable.